A brief review of Bornean banded langur Presbytis chrysomelas (Müller, 1838) of Sarawak - Faezah, Mohammad Noor; Nur Aizatul Izzati, Tukiman; Roberta Chaya Tawie, Tingga; Mohamad Fhaizal, Bukhori; Mohd Azlan, Jayasilan; Denel, Azroie; Badrul Munir, Md Zain; Abdul Latiff, Muhammad Abu Bakar; Mohd Ridwan, Abd Rahman (Department of Environmental Sciences, Arak University, 2023)
The critically endangered Bornean banded langur (Presbytis chrysomelas) is exclusively found in Borneo. This species is classified among the world's 25 most endangered primate species. The geographical locations and distribution patterns of P. chrysomelas remain inadequately understood, and their taxonomic classification remains unclear. Although it was once abundant in Sarawak, the distribution of P. chrysomelas has become one of the most restricted among all Presbytis species. Presently, documented sightings of P. chrysomelas span across five specific locations in Sarawak: Samunsam Wildlife Sanctuary, Tanjung Datu National Park, Gunung Pueh National Park, Similajau National Park, and Maludam National Park. Thus, the purpose of this review is to present previous studies conducted on P. chrysomelas in Sarawak, elucidating its taxonomy, characteristics, distributions, important sites, research gaps, threats, and recommendations for further studies. Immediate conservation efforts and attention from the primatologist, relevant authorities and stakeholders are needed to prevent the localized extinction of P. chrysomelas.